Peningkatan Keterampilan Masyarakat melalui Kegiatan Sosialisasi dan Pelatihan Pembuatan Pupuk Organik Cair dari Kotoran Ternak Sapi (Feces) di Kelurahan Parangluara - Khalilah Nurfadilah; Muh. Algifari Alayubi; Lukmar T; Zulfikar Alifahmi; Putri Saras; Muafikah Tul Azizah; musdalifah; Asmia; Nur Pratiwi Baso; Tiara Anastasya Halik; Nurfadilah; Astrid Putri Shafira (PPM LP2M UIN Alauddin Makassar, 2023)
The purpose of this activity is as an effort to increase community skills through socialization activities and training in making liquid organic fertilizer from cow manure. The time and place for it to be held is Monday, October 31 2022, 14.00-16.00 WITA and is held in the Parangluara village office hall. Socialization and training is a series of continuous activities, where socialization is a process of interaction and learning carried out by someone in a cultural society. While training is an activity to train or develop a skill and knowledge for oneself or others, which is related to certain competencies that are useful. Organic fertilizers are fertilizers composed of living matter, such as weathering of plant, animal and human remains. Cow manure is waste produced by cows. Cow manure consists of cow feces, broom urine, and leftover feed containing high nitrogen. Cow dung is one of the many alternative materials that are easy to find around us, especially in rural areas. This activity resulted in a product in the form of liquid organic fertilizer from cow dung. Keywords: Livestock Manure, Socialization and Training, Organic Fertilizer,